Arabic language learning in a comprehensive approach (theoretical study) - Zera Ilhami; A. Syahid Robbani (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2021)
This study research on how to determine Arabic language learning methods and techniques with a comprehensive approach, with the aim of learners to understand and be able to practice what has been learned and understand four skills thoroughly. This Research is literature research that seeks to find the literature that corresponds to the theme of the discussion and then analyzed with a descriptive analysis. The results of this research show that the comprehensive terms used in education cover a variety of aspects. First, the content of Arabic language learning should be comprehensive. Second, Arabic learning methods must also be comprehensive, the methods used in accordance with the materials submitted in order for the previously determined goals to be achieved. Third, the learning process should occur in the whole educational process. A comprehensive approach is more effectively applied to elementary and intermediate students. As for the advanced level of language teaching, it is more suitable to use Nazhariyah al-Furu'. This approach is how teachers modify the classes they face by sticking to the achievements of the four skills. Therefore, a comprehensive approach that includes strategies, methods, models, and learning elements make four skills in Arabic can be learned to master and develop Arabic comprehensively.Penelitian ini mengkaji tentang cara menentukan metode dan teknik pembelajaran bahasa Arab dengan pendekatan komprehensif, dengan tujuan agar peserta didik mampu memahami dan mempraktikkan apa yang telah dipelajari dan memahami empat keterampilan secara menyeluruh. Penelitian ini merupakan penelitian kepustakaan yang berusaha menemukan literatur yang sesuai dengan tema kajian  kemudian menganalisisnya dengan analisis deskriptif. Hasil penelitian ini menunjukkan bahwa istilah komprehensif yang digunakan dalam pendidikan mencakup berbagai aspek. Pertama, isi pembelajaran bahasa Arab harus komprehensif. Kedua, metode pembelajaran bahasa Arab juga harus komprehensif, metode yang digunakan sesuai dengan materi yang diajukan agar tujuan yang ditentukan sebelumnya tercapai.  Pendekatan komprehensif lebih efektif diterapkan pada siswa dasar dan menengah. Sedangkan untuk tingkat pengajaran bahasa Arab lanjutan, lebih cocok menggunakan Nazhariyah al-Furu'. Pendekatan ini adalah bagaimana guru memodifikasi kelas yang mereka hadapi dengan tetap berpegang pada empat keterampilan yang ada. Oleh karena itu, pendekatan komprehensif yang mencakup strategi, metode, model, dan elemen pembelajaran membuat empat keterampilan dalam bahasa Arab dapat dipelajari untuk menguasai dan mengembangkan bahasa Arab secara komprehensif.